Determination of freedom-from-rabies for small Indian mongoose populations in the United States Virgin Islands, 2019–2020 - Browne, A. Springer; Cranford, Hannah M.; Morgan, Clint N.; Ellison, James A.; Berentsen, Are; Wiese, Nicholas; Medley, Alexandra; Rossow, John; Jankelunas, Leanne; McKinley, Alan S.; Lombard, Claudia D.; Angeli, Nicole F.; et al. (PLOS Neglected Tropical Diseases, 2021)
Author summary Mongooses in the Caribbean region are known to carry rabies and infect and kill humans with the deadly virus. While many countries in the Caribbean region assume they are rabies-free, there is a lack of scientifically based surveillance. We prospectively designed a statistically valid study to determine that mongoose populations in the US Virgin Islands are rabies-free and pose no risk of transmission to human or animal populations. We are pursuing further surveillance efforts to establish rabies freedom in all wildlife and domestic animal population in the US Virgin Islands.